Infection in Burn Wound Patient - Arsita, Elli; Septrilla, Gladys (Jurnal MedScientiae, 2024)
Infection is a major cause of increased morbidity and mortality in burns. It is known that about 67% of wound swab cultures are positive for bacterial infection. Burn infection occurs when the skin as the first line of defense is disturbed so that it becomes a good ground for bacterial growth. Literature review by searching through electronic databases such as PubMed, ProQuest, and Google Scholar with the keywords. Bacteria that are often found to cause burn infection are Pseudomonas aeruginosa (24.95%), Staphylococcus aureus (24.05%), Acinetobacter sp (17.09%), and Klebsiella sp (15.19%). Factors causing infection are age, degree of burn, hospitalization of more than 10 days, drug resistance, and inadequate wound management. The most common pathogen causing burn infection is Pseudomonas aeruginosa, because it can grow in a humid environment. The proper use of definitive antibiotics to fight infection is very important. Piperacillin-Tazobactam, Imipenem, Colistin, and Polymyxin B have high sensitivity to gram-negative bacteria, while Vancomycin and Linezolid are effective against gram-positive bacteria and also in treating MRSA.